Peningkatan Kompetensi Pendidik dalam Literasi Digital Untuk Menghadapi Tantangan Pembelajaran Abad 21 - Angel Dwi Septianingrum; Awalia Marwah Suhandi; Fannia Sulistiani Putri; Prihantini Prihantini (Jurnal Ilmiah Wahana Pendidikan, 2022)
The problems and challenges of education in the 21st century have a very essential urgency because they involve the learning process in the classroom. The problem is the dysfunction between the use of technology and educators in mastering the technology which is useful in 21st century learning. In this study, qualitative methods were used with data collection techniques using various reference journals and books that were relevant to the discussion in the article. The results obtained in this study are educators must be willing and able to try to have several competencies related to the teaching and learning process in the classroom, mastery of these competencies for example is digital literacy in the 21st century. The conclusion in this study is to be able to improve the quality of learning in the classroom. educators can use technology in their learning, this technology can be developed with digital literacy competencies in the midst of the rise of technology in the 21st century. Mastery of teacher competence in digital literacy should pay attention to several aspects such as the characteristics of students, use of technology, and the environment in a learning that puts forward technology-based learning in the 21st century